On Banach ideals satisfying c_0(A(X,Y))=A(X,c_0(Y)) - Delgado, J. M.; Piñeiro, C. (MATHEMATICA SCANDINAVICA, 2008)
We characterize Banach ideals [A,a] satisfying the equality c_0(A(X,Y))= A(X,c_0(Y)) for all Banach spaces X and Y. Among other results we have proved that K (the normed operator ideal of all compact operators with the operator norm) is the only injective Banach ideal satisfying the equality.